Arthur$1 (Bs teacher troubles - Brown, Marc Tolon (Boston : Little, Brown and Company, 1986)
Third-grader Arthur is amazed when he is chosen to be in the school spellathon.
Keywords: Schools -- Fiction; Teachers -- Fiction; Animals -- Fiction